Climate change and computational chemistry: a molecular perspective - Buendía-Atencio, Cristian (2017)
The urgent need to understand the frequent negative changes that the planet Earth suffer on its soil, rivers and atmosphere and the need to mitigate climate change makes computational chemistry stand out as a branch of chemistry that allows thestudy and prediction of different physicochemical properties of several complex molecular systems of environmental significance which are sometimes impossible to study in a laboratory. The present article shows a molecular overview of the behavior and physicochemical characteristics of some atmospheric pollutants studied through computational chemistry.